Flight performance of actively foraging honey bees is reduced by a common pathogen. Issue 5 (7th July 2016) - Wells, Trish; Wolf, Stephan; Nicholls, Elizabeth; Groll, Helga; Lim, Ka S.; Clark, Suzanne J.; Swain, Jennifer; Osborne, Juliet L.; Haughton, Alison J.
Summary: Sudden and severe declines in honey bee ( Apis mellifera ) colony health in the US and Europe have been attributed, in part, to emergent microbial pathogens, however, the mechanisms behind the impact are unclear. Using roundabout flight mills, we measured the flight distance and duration of actively foraging, healthy‐looking honey bees sampled from standard colonies, before quantifying the level of infection by Nosema ceranae and Deformed Wing Virus complex (DWV) for each bee. Neither the presence nor the quantity of N . ceranae were at low, natural levels of infection had any effect on flight distance or duration, but presence of DWV reduced flight distance by two thirds and duration by one half. Quantity of DWV was shown to have a significant, but weakly positive relation with flight distance and duration, however, the low amount of variation that was accounted for suggests further investigation by dose‐response assays is required. We conclude that widespread, naturally occurring levels of infection by DWV weaken the flight ability of honey bees and high levels of within‐colony prevalence are likely to reduce efficiency and increase the cost of resource acquisition. Predictions of implications of pathogens on colony health and function should take account of sublethal effects on flight performance.